2018
DOI: 10.1002/chem.201801155
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution Reactions Catalyzed by a Bis(thiosemicarbazone) Cobalt Complex: An Experimental and Theoretical Study

Abstract: The synthesis and characterization of a dinuclear bis(thiosemicarbazone) cobalt complex [Co L (NCS) ] is reported. This complex exhibits significant catalytic activity for hydrogen production in DMF by using triethylammonium (Et NHBF ) as the proton source. Cyclic voltammetry data allowed a maximum turnover frequency of 130 s for 1 m proton concentration to be determined. The catalytic nature of the process and the production of dihydrogen were confirmed by gas analysis during controlled potential electrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 47 publications
(92 reference statements)
1
76
0
Order By: Relevance
“…In addition to the above main series of HECs, many other well designed ligand platforms have been applied for housing transition metals as HECs. 313,326,[366][367][368][369] For example, the macrocyclic Ni complex 72 and its analogues were good electrochemical HECs under organic-aqueous solutions 370 and fully aqueous solutions. 371 Recent studies demonstrated that dithiolene complexes 73 and the nitrogen donor ligand stabilized complex 74 could efficiently catalyze both electrochemical and photochemical H 2 evolution from water reduction, [372][373][374] and a cobalt bis(iminopyridine) complex 75 could also act as an efficient electrocatalyst for H 2 production from an aqueous solution.…”
Section: Overview Of Molecular Catalysts For Reduction Reactionsmentioning
confidence: 99%
“…In addition to the above main series of HECs, many other well designed ligand platforms have been applied for housing transition metals as HECs. 313,326,[366][367][368][369] For example, the macrocyclic Ni complex 72 and its analogues were good electrochemical HECs under organic-aqueous solutions 370 and fully aqueous solutions. 371 Recent studies demonstrated that dithiolene complexes 73 and the nitrogen donor ligand stabilized complex 74 could efficiently catalyze both electrochemical and photochemical H 2 evolution from water reduction, [372][373][374] and a cobalt bis(iminopyridine) complex 75 could also act as an efficient electrocatalyst for H 2 production from an aqueous solution.…”
Section: Overview Of Molecular Catalysts For Reduction Reactionsmentioning
confidence: 99%
“…20 Metal complexes based on thiosemicarbazone ligands are emerging as a new class of electrocatalyst for HER. [21][22][23][24][25][26] Indeed, it was suggested that the introduction of proton relays in the second coordination sphere of the metal center combined with the use of redox-active ligands can be exploited to enhance or promote catalytic activity. [27][28][29] These complexes thus present some interesting features relevant to electrocatalytic proton reduction: the thiosemicarbazone ligand has already been shown to be redox active while the presence of S-donors and several N-atoms allows for protonation of the ligand and can serve as proton relays.…”
Section: 6mentioning
confidence: 99%
“…Crystal X-ray diffraction analysis revealed that 68 exists as a dimer, which dissociates upon two-electron reduction. 178 Complex 68 is able to catalyse proton reduction when titrated with Et 3 NHBF 4 (pK a = 9.2) in DMF, as it exhibits a TON of 9 with a faradaic yield of 65% under CPE with an applied potential of −1.60 vs. Fc + /Fc for 4 h. Combined electrochemical, theoretical and kinetic ana- lyses suggested a possible catalytic mechanism involving a three-electron-reduced Co(I) species protonated on the coordinating nitrogen of the thiosemicarbazone ligand. The last step of the HER mechanism is the second protonation, proposed by the authors to take place on the Co(I) centre.…”
Section: Macrocyclic Thiolatesmentioning
confidence: 99%